6) Multiply and verify the results for the given values.
(a+b) (2a -3b); a=2,b=-1
Answers
Answered by
0
Answer:
3
Step-by-step explanation:
(2+1)(2×2-3×1)
3×1= 3
Answered by
2
a = 2, b = (-1)
(a+b) (2a -3b)
= 2a² - 3ab + 2ab - 3b²
= 2a² - ab - 3b²
= 2×2² - 2×(-1) - 3×(-1)²
= 8 + 2 - 3
= 7. ...........................................(i)
____________________
a = 2, b = (-1)
(a+b) (2a -3b)
= [2 + (-1)] [2×2 - 3×(-1)]
= [2 - 1] [4 + 3]
= 1 × 7
= 7. ...........................................(ii)
(i) and (ii) are same.
please mark me brainlist
Similar questions